Prenatal diagnosis of urinary track defects - Agnieszka Maria Berendt; Monika Wójtowicz-Marzec (Kazimierz Wielki University, 2019)
Introduction Congenital malformations are the main cause of miscarriage, perinatal mortality and disability among children. According to Polish Registry of Congenital Malformations for 2005-2006 congenital disorders affect 2.0-4.0% of newborns. Heart defects, musculoskeletal abnormalities and urinary track defects are the most common. Purpose The article aims to shortly describe characteristic ultrasound findings concerning certain urinary tract defects. Brief description Renal abnormalities result from complexity of kidneys embriogenesis. Obligatory ultrasound screenings during pregnancy enable early prenatal diagnosis of urinary track defects and it is helpful for planning postnatal or prenatal treatment. Oligohydramos is characteristic for urinary tract congenital disorders. Lack of renal parenchyma, increased echogenicity of renal parenchyma, difficulties in bladder visualisation, cysts within kidneys, hydronephrosis always indicate abnormalities concerning urinary track. Visualisation of urinary track defect obligate further screening for accompanying abnormalities. Sequence of defects, plural abnormalities are indications for genetic evaluation in referral medical centers. Postnatal treatment of congenial urinary track disorders include watchful observation, early surgical treatment or palliative care. The prognosis depends on the type of defect and accompanied anomalies. Summary/conclusion Urinary track defects in prenatal period are very common. Every child suspected for urinary track defect requires detailed evaluation in referral medical center including echocardiography and assessment of karyotype.